Seroprevalence of spotted fever group and typhus group rickettsiae in individuals with acute febrile illness from Gorakhpur, India. (February 2019) - Mane, Arati; Kamble, Suchit; Singh, Manish Kumar; Ratnaparakhi, Manisha; Nirmalkar, Amit; Gangakhedkar, Raman
Highlights: Spotted fever group (SFG) and typhus group (TG) rickettsiae are endemic in Gorakhpur, India. SFG and TG rickettsioses may have roles as potential causes of acute febrile illness and acute encephalitis syndrome outbreaks. SFG IgM positivity was significantly higher among females, while IgG positivity was significantly higher in individuals ≥45 years of age. TG IgM and IgG positivity were significantly higher in individuals involved in outdoor activities and among housewives. Abstract: Background: The aim of this study was to estimate the seroprevalence of spotted fever group (SFG) and typhus group (TG) rickettsiae among individuals with acute febrile illness (AFI) in the scrub typhus endemic district of Gorakhpur in India. This district is one of the worst affected by annual seasonal acute encephalitis syndrome (AES) outbreaks. Methods: Antibodies against SFG and TG rickettsiae and the associated risk factors were determined in 294 individuals presenting with an AFI, encountered during a community-based survey conducted during the AES outbreak period October–November 2016. Results: Respective IgM and IgG seropositivity was 13.6% and 36.7% for SFG, and 7.1% and 15.3% for TG. SFG IgM positivity was significantly higher among females, while IgG positivity was significantly higher among individuals ≥45 years of age. IgM and IgG seropositivity for TG rickettsiae were significantly higher in individuals involved in outdoor activities and housewives, but did not differ according to age group, sex, or educational status. Conclusion: The study results present serological evidence of SFG and TG rickettsiosis, in addition to scrub typhus, among individuals with AFI in Gorakhpur region and indicate the need to explore their roles as potential causes of AES in the region.